Analysis of Photovoltaic Panel Performance Integrated with the Grid in a Load-Sharing Scheme - Aditya, Agellio Farras; Ulinuha, Agus (Faculty of Engineering, Universitas Tanjungpura, 2025)
This paper examines the performance of photovoltaic panels integrated into the electrical grid in a load-sharing scheme at Darool Ehsan Muhammadiyah Senior High School, Sragen. The study is part of Universitas Muhammadiyah Surakarta's community service program focused on renewable energy development in educational environments. Unlike previous studies relying on simulated data, this research uses real-time primary data from direct measurements of photovoltaic power production and grid electricity consumption over a specific period. The study